The Effectiveness of Early Detection by the Social Cultural Unit in Preventing Conflict Between Silat Colleges at the Jombang Police - Santoso, Alvian (Advances in Police Science Research Journal, 2024)
This research will focus on early detection operational activities in the form of Jombang Police Satintelkam intelligence investigations in preventing conflict between silat schools. This is due to the increasing cases of conflict between martial arts schools in Jombang Regency. The concepts used are early detection, intelligence, intelligence investigation, conflict prevention and operational management of intelligence and security. The theories used in this research are competency theory, human needs theory, and work effectiveness theory. Apart from that, this research also uses POK in the form of Law Number 2 of 2002, Perpol Number 2 of 2021, and Perkabik Number 1 of 2023. The results of the research show that the competence of the Satintelkam Social and Cultural Unit personnel is still not optimal. The background that is the root of the problem of conflict between silat schools is the ego of college members in the presence of a community, fanaticism towards monuments, and lack of leadership supervision of members. Then, the implementation of early detection by the Social and Cultural Unit is still not effective. From the research that has been carried out, it can be concluded that steps are needed to make personnel competence and the performance of intelligence investigations in the Socio-Cultural Unit optimal and effective. In this way, the Satintelkam Social and Cultural Unit can make a greater contribution in handling conflicts between silat schools in the Jombang Regency area.